2014
DOI: 10.2116/analsci.30.707
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-elastic Laser Scattering for Measuring Inhomogeneous Interfacial Tension in Non-equilibrium Phenomena with Convective Flows

Abstract: An inhomogeneous distribution of interfacial tension can induce different types of non-equilibrium spontaneous motion at the interface by convective flow, or by the solutal Marangoni effect. Several applications of the quasi-elastic laser scattering (QELS) method used to study these effects are presented here. The relationship between the interfacial tension and the non-equilibrium phenomena has been verified experimentally for each application. In a water/nitrobenzene oscillatory system with continuous surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 62 publications
(99 reference statements)
0
13
0
Order By: Relevance
“…14,15 The technique relies on two phenomena to achieve aerosol droplet capture and surface tension analysis, the first is the use of a focused laser that acts as an optical tweezer, and the second is the use of quasi-elastic laser scattering (QELS). [32][33][34][35][36][37][38][39][40] Spontaneous spherical resonance occurs as a result of thermal fluctuations at the surface of the liquid droplet, which can be observed in the Hz range of frequencies in a QELS spectrum. Figure 6 shows the experimental setup used to immobilize aerosol droplets using an optical tweezer as well as the use of QELS to analyze the spherical resonance modes at the droplet surface.…”
Section: Spontaneous Capillary Wave Resonance and Light Scattering Mementioning
confidence: 99%
“…14,15 The technique relies on two phenomena to achieve aerosol droplet capture and surface tension analysis, the first is the use of a focused laser that acts as an optical tweezer, and the second is the use of quasi-elastic laser scattering (QELS). [32][33][34][35][36][37][38][39][40] Spontaneous spherical resonance occurs as a result of thermal fluctuations at the surface of the liquid droplet, which can be observed in the Hz range of frequencies in a QELS spectrum. Figure 6 shows the experimental setup used to immobilize aerosol droplets using an optical tweezer as well as the use of QELS to analyze the spherical resonance modes at the droplet surface.…”
Section: Spontaneous Capillary Wave Resonance and Light Scattering Mementioning
confidence: 99%
“…The apparatus used for the QELS measurement has been described in detail elsewhere. 13,15 Samples were irradiated with a beam from a Nd-YVO4 laser (JUNO 100, Showa Optronics Co., Japan) that was separated into 95 and 5% power beams by a beam splitter, and the 95% segment was introduced to a water/ chloroform or water/air interface through a focusing lens. In all experiments, measurements were conducted in a quartz cell of 23 mm × 23 mm × 49 mm.…”
Section: Apparatusmentioning
confidence: 99%
“…We focused on the quasi-elastic laser scattering (QELS) method that allows non-contact measurements of interfacial tension and has a time resolution of seconds. 13,14 We have used the QELS method to measure interfacial tension changes for the process of lysosome adsorption to a lipid membrane formed at a water/chloroform interface. 15 It has been found that the changes of the interfacial tension were observed within a few seconds through the electrostatic interaction between lysozyme and lipid membranes, and that adsorption behaviors of DOPC and DOPS membranes were different, depending on the charges of lipid membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The determination of electrocapillary data requires in situ measure- via University of Ottawa OCUL ment of interfacial tension in order to determine the influence of the applied electrical potential over the surface pressure. Many techniques have been tested over the years such as drop shape analysis [23,24], drop-weight determination [25], quasi-elastic light scattering [26][27][28][29] (QELS) and Wilhelmy plate [30] based methods. Among all these methods QELS is the only non-invasive method that does not require time-consuming procedures and gives reproducible and reliable results.…”
Section: Introductionmentioning
confidence: 99%